2021
DOI: 10.1093/ajhp/zxab180
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of the unwarranted continuation of antipsychotics for the management of ICU delirium during transitions of care: A multicenter evaluation across New Jersey

Abstract: Purpose Nearly half of intensive care unit (ICU) patients will develop delirium. Antipsychotics are used routinely for the management of ICU delirium despite limited reliable data supporting this approach. The unwarranted continuation of antipsychotics initiated for ICU delirium is an emerging transitions of care concern, especially considering the adverse event profile of these agents. We sought to evaluate the magnitude of this issue across 6 centers in New Jersey and describe risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The most commonly implicated medications include antipsychotics and acid-suppressive therapies. [1][2][3][4][5] A multicenter, prospective cohort study demonstrated that 24% of patients treated with antipsychotics in the ICU were prescribed one at discharge. 1 Several other studies have demonstrated the inappropriate continuation of antipsychotics initiated in the ICU upon discharge to the floor and ultimately hospital discharge with prescribing rates ranging from approximately 26% to 84% and 29% to 61%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly implicated medications include antipsychotics and acid-suppressive therapies. [1][2][3][4][5] A multicenter, prospective cohort study demonstrated that 24% of patients treated with antipsychotics in the ICU were prescribed one at discharge. 1 Several other studies have demonstrated the inappropriate continuation of antipsychotics initiated in the ICU upon discharge to the floor and ultimately hospital discharge with prescribing rates ranging from approximately 26% to 84% and 29% to 61%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several other studies have demonstrated the inappropriate continuation of antipsychotics initiated in the ICU upon discharge to the floor and ultimately hospital discharge with prescribing rates ranging from approximately 26% to 84% and 29% to 61%, respectively. [2][3][4] Additionally, Wohlt and colleagues demonstrated that 60% of patients were inappropriately continued on an acidsuppressive agent at ICU discharge and 24.4% at hospital discharge. 5 Inappropriate continuation of these medications may lead to an increased risk of adverse effects and greater healthcare-related costs.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen studies examined the use of psychotropic medications in survivors of critical care (online supplemental file S3, table 3). 33–46 Drugs included were antipsychotic and anxiolytic agents alongside antidepressants. Twelve studies examined psychotropic medications use in critical care survivors at hospital discharge;34–45 one study examined their use up to 180 days following hospital discharge33 and the final study examined the use of these medications up to 1 year posthospital discharge 46…”
Section: Resultsmentioning
confidence: 99%
“…Across the studies, in those patients prescribed psychotropic medications during admission, there was wide variation in the continued use of these drugs at hospital discharge (range 10.30–61%), although the appropriateness of this continued use was difficult to assess across the studies 34–45. Four studies gave details on the prescription appropriateness at hospital discharge; one single centre US study found 54 of their cohort of 161 patients (34%) had been continued on antipsychotics or anxiolytics at hospital discharge, with no patient having a documented reason for their use 37.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation